Estimation of Sport Facilities by Means of Technical-Economic Indicator - Hanák, Tomáš; Hrstka, Lukáš; Tuscher, Martin; Biolek, Vojtěch (De Gruyter, 2020)
This paper is concerned with early cost estimation of sport facilities. Sufficiently precise cost estimation is essential for investors in the pre-investment stage where they decide on whether to pursue an investment and choose a suitable technical solution for the development of the project. Through a detailed analysis of the technical and economic documentation pertaining to seven sport facilities projects assembled using concrete prefabricated beam parts, as well as evaluation of the data thus obtained, three types of technical-economic indicators were set in relation to the enclosed building area, the number of spectator seats and the sports playing area. The results achieved indicate that evaluation of relations between these three indicators could contribute to a more effective use of investment funding on the part of the investor. Other conclusions include the finding that available indicators published by private companies active in the area of construction budgeting are not sufficiently accurate for the purposes of investment decision-making; specifically, these indicators greatly overestimate the costs of sport facilities, which can potentially lead to these projects being rejected. This contribution brings know-how for a more accurate early cost estimation of sport facilities in the Czech Republic which can, thanks to a generally applicable methodology, be used in other countries as well.

This paper is concerned with early cost estimation of sport facilities. Sufficiently precise cost estimation is essential for investors in the pre-investment stage where they decide on whether to pursue an investment and choose a suitable technical solution for the development of the project. Through a detailed analysis of the technical and economic documentation pertaining to seven sport facilities projects assembled using concrete prefabricated beam parts, as well as evaluation of the data thus obtained, three types of technical-economic indicators were set in relation to the enclosed building area, the number of spectator seats and the sports playing area. The results achieved indicate that evaluation of relations between these three indicators could contribute to a more effective use of investment funding on the part of the investor. Other conclusions include the finding that available indicators published by private companies active in the area of construction budgeting are not sufficiently accurate for the purposes of investment decision-making; specifically, these indicators greatly overestimate the costs of sport facilities, which can potentially lead to these projects being rejected. This contribution brings know-how for a more accurate early cost estimation of sport facilities in the Czech Republic which can, thanks to a generally applicable methodology, be used in other countries as well.
Estimation of Sport Facilities by Means of Technical-Economic Indicator
Keywords: cost; estimation; indicator; sport facilities; cost; estimation; indicator; sport facilities